Cottonseed Malate Synthase : Purification and Immunochemical Characterization - Trelease, Richard N. (1987)
Malate synthase (EC 4.1.3.2), an enzyme unique to the glyoxylate cycle, was purified to homogeneity from cotyledons of 72-hours, darkgrown cotton (Gossypium hirsutum L.) seedlings. Homogeneity of the enzyme was assessed by silver staining SDS-PAGE gels. Purification was accomplished by using a single buffer medium through six steps involving one ammonium sulfate fractionation and chromatography on three columns (Sephacryl S-300, DEAE Sephacel, Phenyl Sepharose). Large-scale preparation of glyoxysomes, a main step in all other published procedures, was not involved. The purified enzyme and that extracted from glyoxysomes appears to be a dodecamer with a native molecular weight of 750,000 (sedimentation coefficient of >20 Svedberg units [S] on sucrose gradients) composed of identical subunits (molecular weight approximately 63,000). The monomer (5S) occurs in the cytosol. Polyclonal antibodies raised in rabbits were judged to be monospecific for malate synthase by immunotitration, double immunodiffusion, and western blotting. Double immunodiffusion experiments revealed only partial immunological identity between the 5S (cytosolic) and 20S (glyoxysomal forms, although complete identity was observed between the 5S form in immature and germinated seeds, and the 20S form in immature and germinated seeds. Cross-reactivity of the cotton antimalate synthase serum was observed with extracts from five other oilseeds. Western blot analyses showed that malate synthase protein was not present in immature seeds prior to appearance of enzyme activity, but when present, subunit molecular weight was indistinguishable in immature, desiccated, and germinated seeds.